If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -1 = 0 Reorder the terms: -1 + 6y = 0 Solving -1 + 6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 6y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 6y = 0 + 1 6y = 0 + 1 Combine like terms: 0 + 1 = 1 6y = 1 Divide each side by '6'. y = 0.1666666667 Simplifying y = 0.1666666667
| 0.3x-17=1.1x-25 | | 4/5x-1/5=9 | | 2(x+5)=36 | | 3x(x-2)+(x-2)= | | 3a+5+4a-6=2 | | x^2-10+11=0 | | -5-1.2= | | 2*log*x=log*2+log(3*x-4) | | 10+x-7x=-38 | | 8x+6(1+5x)=2 | | 6.1+1= | | 7+7k=147 | | 2/3m-1/3=5/12 | | 8-3y=2(3+y)-5 | | -2(n-4)=10-2N | | -2y-5+2y^2=0 | | 8x+6(1+5x)= | | 4-2(2w-3)=6w-90 | | -6-4=-7a-5 | | 5/2x=(x-5) | | y=3sinx+2cosx | | a+a+5.80+0.5(5.80+a)+3(0.5(5.80+a))=246.20 | | 5+3(n+1)=2n | | 5z^2(z^2+2)=24-16z^2 | | -6x+10=15-6x | | 3x(2+3y)= | | 5-4(10+8m)=39+5m | | (5x)/(3iy)=5-6i | | x(x+3)-6(x+3)=0 | | (y-x)(y+11x)=a^2-b^2 | | c+8+2c=-10 | | -60=-6+6a |